1960
DOI: 10.1021/jm50011a001
|View full text |Cite
|
Sign up to set email alerts
|

On the Mechanism of Absorption of Drugs from the Gastrointestinal Tract

Abstract: The question of how drugs pass from the gastrointestinal tract into the bloodstream is of vital interest to the pharmacologist and the medicinal chemist, but until recently little progress has been made in unravelling this seemingly complex problem. The literature abounds with reports of the absorption of drugs, but the 23 343

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0
1

Year Published

1970
1970
2010
2010

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 128 publications
(34 citation statements)
references
References 6 publications
1
32
0
1
Order By: Relevance
“…Studies of drug absorption have shown that lipid-soluble, unionized molecules readily penetrate the intestinal epithelium (see Schanker 1960), and it has been suggested that there is an optimal partition coefficient (octanol/buffer) for intestinal absorption of xenobiotics (Houston, Upshall and Bridges 1974).…”
Section: Lipid-solubility and Intestinal Absorption During Enterohepamentioning
confidence: 99%
“…Studies of drug absorption have shown that lipid-soluble, unionized molecules readily penetrate the intestinal epithelium (see Schanker 1960), and it has been suggested that there is an optimal partition coefficient (octanol/buffer) for intestinal absorption of xenobiotics (Houston, Upshall and Bridges 1974).…”
Section: Lipid-solubility and Intestinal Absorption During Enterohepamentioning
confidence: 99%
“…Although phosphanilic acid (pK., 1.8 to 2) (3) readily redissolved when the pH was raised from 1.2 to 6.2, it would exist primarily in the ionized form (99.99%) in the intestine at pH 6 to 8. Therefore, the lack of oral absorption was also related to low membrane permeability as a result of extensive in situ ionization at the site of absorption (11). The prolongation in Tmax could be indicative of diffusion-limited absorption of the ionized species from the subcutaneous site and dissolution-limited absorption of precipitated free acid in the gastrointestinal tract at the highest dose level studied.…”
Section: Resultsmentioning
confidence: 95%
“…The absorption of PEA from the jejunum appears to be a passively mediated process, which is influenced by blood flow. The order of PEA absorption rates from the different gut regions (colon > ileum > jejunum) can be explained in terms of the pH partition hypothesis (Schanker 1960). PEA has a pK, of 9-83 (Hong & Connors 1968) and the proportion of nonionized drug will therefore increase with the increase in pH from jejunum to ileum to colon.…”
Section: Discussionmentioning
confidence: 99%